2001
DOI: 10.1149/1.1406995
|View full text |Cite
|
Sign up to set email alerts
|

Control of Agglomeration on Copper Seed Layer Employed in the Copper Interconnection

Abstract: This paper describes the control and reduction of agglomeration of the thin copper seed layer deposited on different barrier layers. Higher stress is applied in layers deposited on TaN and Ta barrier layers. This stress greatly affects the agglomeration and adhesion strength. This stress can be reduced markedly with employing a TaSiN barrier layer instead of Ta barrier layer. Correlations have been found between the stress in as-deposited copper seed layer and the agglomeration height formed with this annealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 5 publications
2
48
0
Order By: Relevance
“…8 Control of the agglomeration is required in thin copper seed layer because this agglomeration strongly affects the ͑111͒ orientation and the adhesion of copper electroplating layer. 5,6 To study these details, a thin ͑10 nm͒ copper seed layer was deposited on different barrier layers and was annealed at 400°C. Surface morphology was observed by the scanning electron microscope ͑ϫ20,000͒.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Control of the agglomeration is required in thin copper seed layer because this agglomeration strongly affects the ͑111͒ orientation and the adhesion of copper electroplating layer. 5,6 To study these details, a thin ͑10 nm͒ copper seed layer was deposited on different barrier layers and was annealed at 400°C. Surface morphology was observed by the scanning electron microscope ͑ϫ20,000͒.…”
Section: Resultsmentioning
confidence: 99%
“…Adhesion strength of thick copper conductive layer and agglomeration of the copper seed layer are also influenced by the ͑111͒ orientation and by the stress of seed layer as reported elsewhere. 5,6 Although the control of the ͑111͒ orientation is very important in the copper conductive layer, few papers have reported the control of ͑111͒ orientation in the electroplating layer. This paper describes the control of ͑111͒ orientation in electroplating copper layer.…”
mentioning
confidence: 99%
“…25b). The bigger Cu grain size can be attributed to the higher mobility of Cu on α-Ta than on β-Ta [52].…”
Section: -P17mentioning
confidence: 99%
“…7,8 Although the control of this stress is important in multilevel copper interconnection, few papers have reported on this aspect. 7 Ta and TaN layers have been extensively used as adhesion ͑substrate͒ layers for the copper seed layer. However, a high stress and an higher stress are applied at the Cu/Ta and Cu/TaN interface are obtained in thin copper seed layers, as reported elsewhere.…”
mentioning
confidence: 99%
“…It has been reported that a very low adhesion strength is obtained for the copper conductive layer when the layer is electroplated on such highly stressed seed layers, despite the fact that the surface appears smooth. 7 For optimum interconnects, the deposition of low stress and highly ͑111͒ oriented copper seed layers is required before the sputtering of the copper seed layer. It has been shown that a much lower stress layer can be deposited on TaSiN barrier layers.…”
mentioning
confidence: 99%